Successful Pregnancy and Delivery after Premature Ovarian Insufficiency Combined with Undifferentiated Connective Tissue Disease: A Case Report - Du, Mengyang; Peng, Liying; Zhang, Ruixiu; Bao, Shihua (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2024)
Background: Premature ovarian insufficiency (POI) is extremely rare in the early stage of undifferentiated connective tissue disease. Patients with POI find it difficult to achieve successful pregnancy and delivery. Case Presentation: A 27-year-old female visited an outpatient department for premature ovarian insufficiency (POI) and infertility. She had regular menstrual periods since she was 14 years old and had no history of systemic disease. Laboratory tests showed low estrogen (15 ng/L, range 19.6-144.2 ng/L), elevated follicle-stimulating hormone (34 U/L), low anti-Mullerian hormone (0.1 μg/L), normal prolactin (11.48 ng/mL), and thyroid stimulating hormone (TSH) levels (0.97 mU/L). She demonstrated smaller bilateral ovarian volume and positivity to antinuclear and antiphospholipid antibodies. After the failure of conventional drug therapy and in vitro fertilization, the patient became pregnant naturally after treatment with glucocorticoids. Conclusion: Immunosuppression could help improve ovarian function and pregnancy outcomes in POI patients, but the therapeutic mechanisms are not clear and should be elucidated with more clinical studies.
Keywords: Premature ovarian insufficiency (POI)